Therapy adherence in elderly of Northern Portugal - Pinto, Isabel C. (2018)
The elderly population has been growing significantly, leading to an increased prevalence of chronic diseases and consequent taking medication. The complex therapies of elderly can lead to therapy non-adherence, increasing several health risks. Aim This study aimed to estimate the prevalence of therapy adherence and associated factors. Material and Methods This cross-sectional study was based on a questionnaire, with MAT scale (measure of adherence to therapy) validated for the Portuguese population (Lima, 2001) based on the Morisky scale, applied to 52 elderly (≥65 years) from northern Portugal. To assess therapy adherence, those whose average adherence levels were ≥5, were called adherent. It was used descriptive statistics. The level of association between categories of variables was studied through the adjusted residuals (AdR) and the relationship between adherence to the therapeutic and the number of medications taken per day was studied using the Mann-Whitney U test, with a significance level of 5%. The study was approved by Ethics Committee. Results The sample consisted mainly of males elderly (61.5% vs. 38.5%), aged between 67 and 98 years (mean 82.71), and while 48.1% was between 75–84 years old. The participants shows high therapy adherence (96.2%). The non-adherent elderly are related to self-medication (AdR=4.3), with the high level of cholesterol (AdR=2.9) and chronic pain (AdR=2.9). The non-adherent elderly seem tend to take more drugs per day, although not statistically significant (P = 0.063). Conclusions This study shows that a large prevalence of elderly adhered to the therapy prescribed. Self-medication, having high cholesterol and chronic pain and higher number of different drugs per day seem related to non-adherence.